1980
DOI: 10.1002/1097-4679(198007)36:3<672::aid-jclp2270360311>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Structure of depression in older men and women

Abstract: Administered the Wakefield Self‐Assessment Depression Inventory to 173 noninstitutionalized men and 329 noninstitutionalized women over 59 years of age. Separate, principal factor analyses were performed for both sexes, and the resultant factors were compared between sexes. The elderly men and women shared common dimensions of anxious depression and general dissatisfaction. There was also a suggestion that there might be a third dimension for women–sleep impairment. Implications of the results for diagnosing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Taken altogether, this answers the central question of this paper: the gender difference in depression, with women more likely to be depressed than men, is found in people over the age of 60. (See Table S1 in Supplemental Materials for the full list of articles reviewed, e.g., [20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70]).…”
Section: Epidemiology Of the Gender Difference In Depression In Olmentioning
confidence: 99%
“…Taken altogether, this answers the central question of this paper: the gender difference in depression, with women more likely to be depressed than men, is found in people over the age of 60. (See Table S1 in Supplemental Materials for the full list of articles reviewed, e.g., [20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70]).…”
Section: Epidemiology Of the Gender Difference In Depression In Olmentioning
confidence: 99%
“…et al, 1964), little research interest has been shown in developing instruments to identify and measure emotional states in the elderly. The validity of existing self-report measures of depression with elderly sub jects has recently been questioned by several studies (Blumenthal, 1975;Harmatz and Shader, 1975; Zemore and Eames, 1979;Oltman et al, 1980). These have indicated that the pattern of response to such self-report measures by elderly subjects is distorted by the overlap between typical depressive symptomatology and changes associated with the ageing process itself.…”
mentioning
confidence: 99%
“…different study methods, criteria used and the age distribution in the studied population, see reviews by Gunner-Svensson & Jensen ( 3 ) and Gurland (4). High prevalence rates primarily stem from studies based on the subjects filling in a questionnaire (2,5,6). The method of using questionnaires for case identification is discussed in detail by Goldberg (7).…”
Section: Received April 7 1982; Accepted For Publication September mentioning
confidence: 83%